PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIB SMPIT AL-FITYAH PEKANBARU - Suriyati, Suriyati; Jalinus, Jalinus; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is classroom action research which aims to improve the learning process and the result of learning mathematics by applying Discovery Learning model. The subject of this research were the students in the class VIIB of SMPIT Al-Fityah Pekanbaru that consist of 25 girls at the second semester of academic year 2017/2018. Instruments on this reserach constisted of syllabus, lesson plans and worksheets, and instruments of data collection which is observation sheets and the test result sheets. The function of observation sheet is to obtain data from the learning process, while the function of results sheet of the mathematics learning tests is to obtain the results of the study. The descriptive of observation sheets and students’ mathematic tests showed an improvement of learning process prior to the action on the first and second cycles and improve the students’ achievement of learning mathematic. On the knowledge competence, from the basic score of 11 students or 44% increased to 16 students or 64% in the first cycle and increased to 19 students or 76% in Cycle II. On the skills competence, the number of students who reach the minimum criteria of mastery learning from Cycle I of 5 students or 20% improve to 11 students or 44% in cycle II. Based on the results of this research can be concluded that the implementation of the Discovery Learning model can improve the learning achievement of the second semester students of class VIIB of SMPIT Al-Fityah Pekanbaru in the second semester academic year 2017/2018.Keywords: Students’ Math Achievement, Discovery Learning Model, Clasroom Action Research.